Determinant of stunting among children under five years old in Wukirsari Village, Cangkringan Subdistrict, Sleman, Yogyakarta - Vika Indah Rahayu; Nugroho Susanto; Ayu Fitriani (Universitas Respati Yogyakarta, 2019)
Background: One of the biggest nutritional problems in Indonesia is stunting. Children under five years old with stunting are more susceptible to disease and having reduced cognitive abilities. Stunting can be caused by several factors, such as from both external and internal factors. Objective: To find out the determinants of the incidence of stunting among children under five years old in Wukirsari Village, Cangkringan sub district, Sleman, Yogyakarta. Methods: This study was conducted in 23 subvillages in Wukirsari Village in February 2019 with a case control design. This study involved 100 children under five years old with 50 cases and 50 controls. Maternal nutritional status during pregnancy, mothers’ education, family income, and posyandu visit were collected using a questionnaire. Data were analyzed using Chi Square test. Results: There was no correlation between mother’s education and posyandu visit with stunting incidence (p>0.05). There was a correlation between family income with stunting incidence (p=0.00). Family who had low income were 6.526 times more likely to have stunted children. Conclusion: There was a significant correlation between family income with stunting incidence.